Sliding wear behavior of the WC/FeAl-B intermetallic matrix composites at high temperatures - Mohammad Mottaghi (Elsevier, 2021)
In this research, the sliding wear of sintered WC/40 vol% (FeAl-B) composites was studied at high temperatures. It is expected that the wear behavior of WC/FeAl can be improved in the presence of boron at high temperatures. The composites contained different amounts of boron and alumina was chosen as the counter body material in the wear tests. The tests were carried out at temperatures ranging from ambient to 600 °C so that the effect of boron and temperature on wear resistance could be specified. The results showed that while hardness slightly decreased with increasing the boron content to 500 ppm in the FeAl-B matrix, the fracture toughness increased significantly. The maximum wear resistance of the WC/FeAl-500 ppm B composite was recorded at all the temperatures examined. Investigations of the wear surfaces showed that while the wear mechanism of the WC/FeAl-B composites was an abrasive one at room temperature and 300 °C, a more adhesive wear mechanism was detected at 400 °C and a matrix oxidation mechanism was observed at 600 °C. Resumen: En esta investigación, se estudió el desgaste por deslizamiento de los compuestos sinterizados WC/40vol% (FeAl-B) a altas temperaturas. Se espera que el comportamiento de desgaste de WC/FeAl pueda mejorarse en presencia de boro a altas temperaturas. Los compuestos que contenían diferentes cantidades de boro y alúmina se eligieron como material del cuerpo del contador en las pruebas de desgaste. Las pruebas se llevaron a cabo a temperaturas que varían desde la temperatura ambiente hasta 600 °C, de modo que se pudiera especificar el efecto del boro y la temperatura sobre la resistencia al desgaste. Los resultados mostraron que si bien la dureza disminuyó ligeramente al aumentar el contenido de boro a 500 ppm en la matriz de FeAl-B, la tenacidad a la fractura aumentó significativamente. La resistencia al desgaste máxima del compuesto WC/FeAl-500 ppm B se registró a todas las temperaturas examinadas. Las investigaciones de las superficies de desgaste mostraron que, si bien el mecanismo de desgaste de los compuestos WC/FeAl-B era abrasivo a temperatura ambiente y 300 °C, se detectó un mecanismo de desgaste más adhesivo a 400 °C y se observó un mecanismo de oxidación de lamatriz a 600 °C.